2021
DOI: 10.3390/plants10091937
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Glucose in Hydrogen Gas-Medicated Adventitious Rooting in Cucumber

Abstract: Hydrogen gas (H2) and glucose (Glc) have been reported as novel antioxidants and signal molecules involved in multiple biological processes in plants. However, the physiological roles and relationships of H2 and Glc in adventitious rooting are less clear. Here, we showed that the effects of different concentrations Glc (0, 0.01, 0.05, 0.10, 0.50 and 1.00 mM) on adventitious rooting in cucumber were dose-dependent, with a maximal biological response at 0.10 mM. While, the positive roles of hydrogen rich water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This study found that 50% HRW could reduce the starch content and increase the content of water-soluble carbohydrate, sucrose, glucose, and fructose in Lanzhou lily scales (Figure 5). HRW treatment promoted the occurrence of cucumber adventitious roots by increasing glucose, sucrose, and water-soluble carbohydrate content [41]. Huang et al [38] found that HRW could accelerate starch degradation and increase sugar accumulation to promoted seed germination in cucumber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study found that 50% HRW could reduce the starch content and increase the content of water-soluble carbohydrate, sucrose, glucose, and fructose in Lanzhou lily scales (Figure 5). HRW treatment promoted the occurrence of cucumber adventitious roots by increasing glucose, sucrose, and water-soluble carbohydrate content [41]. Huang et al [38] found that HRW could accelerate starch degradation and increase sugar accumulation to promoted seed germination in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose content was determined according to Zhao et al [41]. Lily scales (0.5 g) were thoroughly ground with distilled water.…”
Section: Measurement Of Starch Water-soluble Carbohydrate Sucrose Glu...mentioning
confidence: 99%
See 1 more Smart Citation
“…After this step, the seeds in the tray were moved to the incubator with illumination with a 14 h photoperiod (the photosynthetically active radiation was 200 μmol m −2 s −1 ) at 25 ± 1 °C for 7 d, and the filter paper was kept wet in the tray during this period. The primary roots of explants were carefully cut off after 7 d. In accordance with Zhao et al [ 57 ], the induction of adventitious roots was completed 48 h after treatment. Hence, the cucumber explants were placed in Petri dishes with different treatments and allowed to grow for 48 h. The temperature and photoperiod conditions were the same as the above conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms in the cells, which enable H 2 to have its effects, were also the focus of papers in this SI. Zhao et al [ 25 ] show an interaction between H 2 and glucose in adventitious roots of cucumber. The effects of HRW were blocked by glucosamine, suggesting that glucose content may be mediating root development.…”
Section: Mechanisms Of H 2 Actionmentioning
confidence: 99%